Selected Papers from CUBANNI 2017-"The Fourth International Workshop of Neuroimmunology" - Maria De los Angeles Robinson Agramonte (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Starting from the most interesting papers presented at CUBANNI 2017, the First International Meeting of the Cuban Network of Neuroimmunology, this eBook covers the most up-to-date findings on neuroimmunology research. The topics of the selected papers range from clinical to pre-clinical models, as well as in vitro basic research. Scientific areas covered are autism spectrum disorders, epilepsy, Parkinson's disease, and seizures, with emphasis on epigenetics and experimental models. Neuroinflammation, neuroplasticity, and neurodegenerative processes, biomarker discovery, and the molecular pathways involved are proposed. Additionally as one of the most current and relevant topics published, Tamara da Silva Vaccaro et al proved relevant results on "Alterations in the MicroRNA and their effects on Epigenetic Regulation and Potential Biomarkers in ASD" and Lázaro Gómez et al also published interesting results on Non-Invasive Brain Stimulation for Children with Autism Spectrum Disorders.